Research and Application of Distributed Automatic Test Technology for Line Longitudinal Difference - DING Jin-jin; XU Chen; SUN Hui; WANG Xun-ting; HAN Min-chou (Journal of Harbin University of Science and Technology, 2022)
Aiming at the problems of the joint debugging test of optical fiber differential protection, the two terminal testers can not achieve synchronous control, and carry out the fault test of both sides and automatic test of ratio braking characteristics. By using PTP synchronization technology, the distributed test system of line longitudinal difference and the communication model of synchronous control are established, and the distributed test method of double-terminal synchronous control is studied. Compared with GPS, there are some disadvantages, such as wiring trouble, weak timing signal, unable to form a unified test report and so on. The distributed test system of line longitudinal difference based on PTP synchronization realizes the functions of two terminal synchronous tests, single terminal control and comprehensive evaluation of test results. It can test the fault and braking characteristic curve outside the two sides, and improves the comprehensiveness of on-site debugging.